Southeastern Field Cricket, Gryllus rubens Scudder (Insecta: Orthoptera: Gryllidae) - T.J. Walker (EDIS)
This document provides a comprehensive profile of the southeastern field cricket, Gryllus rubens. It covers the cricket's distribution, identification, life cycle, habitat, and song. The article highlights the cricket's unique trilling song, its presence in lawns, roadsides, and pastures, and its abundance in spring and fall. It also discusses the cricket's role in hybridization with other species and its economic impact. The document is part of the Featured Creatures collection, aimed at both laypersons with some biological knowledge and academic audiences. Published: January 1999.